2020
DOI: 10.1021/acsnano.0c00129
|View full text |Cite
|
Sign up to set email alerts
|

All-Soft Supercapacitors Based on Liquid Metal Electrodes with Integrated Functionalized Carbon Nanotubes

Abstract: Soft energy storage devices, such as supercapacitors, are an essential component for powering integrated soft microsystems. However, conventional supercapacitors are mainly manufactured using hard/brittle materials that easily crack and eventually delaminate from the current collector by mechanical deformation. Therefore, to realize all-soft supercapacitors, the electrodes should be soft, stretchable, and highly conductive without compromising the electrochemical performance. This paper presents all-soft super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 58 publications
0
37
0
Order By: Relevance
“…[ 4,5 ] The realization of liquid metal‐based, integrated systems will be a significant milestone toward high‐performance, integrated electronic skin for applications such as tattoo electronics and human organs‐on‐chips. [ 6,7 ] In recent years, liquid metal has sparked revolutionary progress for many components in electronic skin, including wearable electrodes/circuits, [ 8,9 ] interconnects, [ 10 ] switches, [ 11 ] and actuators. [ 12,13 ] However, an essential “piece of the puzzle” for liquid metal‐based, integrated electronic skin is still missing, which is highly sensitive electromechanical sensors.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4,5 ] The realization of liquid metal‐based, integrated systems will be a significant milestone toward high‐performance, integrated electronic skin for applications such as tattoo electronics and human organs‐on‐chips. [ 6,7 ] In recent years, liquid metal has sparked revolutionary progress for many components in electronic skin, including wearable electrodes/circuits, [ 8,9 ] interconnects, [ 10 ] switches, [ 11 ] and actuators. [ 12,13 ] However, an essential “piece of the puzzle” for liquid metal‐based, integrated electronic skin is still missing, which is highly sensitive electromechanical sensors.…”
Section: Introductionmentioning
confidence: 99%
“… (B,ii) Voltammetry cycle respect to number of cells tested. (B,iii) Reproduced with Permission ( Kim et al., 2020e ). Copyright, American Chemical Society.…”
Section: Lm-based Energy-harvesting and Storage Devicesmentioning
confidence: 99%
“…With an aid of LM alloy, Kim et have demonstrated that all soft supercapacitors can be constructed by synergistically combining it with an oxygen functionalized carbon nanotube (O-CNT) ( Kim et al., 2020e ). The EGaIn (≈1.5 μm) as an LM electrode is stamped onto paper-textured PDMS substrate layer first to serve as a support electrode for O-CNT electrode and form a strong bonding with its native oxide ( Figure 7 Bi) ( Kim et al., 2020e ). Thus, this proposed architecture can withstand applied strains without delamination between high conductive electrical pathways and 3D CNT network.…”
Section: Lm-based Energy-harvesting and Storage Devicesmentioning
confidence: 99%
“…Liquid metal power sources have been demonstrated to achieve flexibility and stretchability while maintaining electrical performance stability and high sensitivity, which presents a better alternative for self‐powered and deformable devices than conventional power sources. These liquid metal‐based deformable power sources include using liquid metal electrodes for all‐soft supercapacitors that are electrochemically and mechanically stable, [ 147 ] liquid metal batteries that are operational at room temperature, [ 148 ] and energy storage batteries employing liquid metal electrodes. [ 149 ] State‐of‐the‐art liquid metal power sources generally take one of three forms: triboelectric generators, thermoelectric generators, and magnetic field harvesting devices.…”
Section: Power Sourcesmentioning
confidence: 99%